#### Question

Prove that : `int sqrt(a^2-x^2)dx=x/2sqrt(a^2-x^2)=a^2/2sin^-1(x/a)+c`

clickto share

#### Solution

You need to to view the solution

Is there an error in this question or solution?

#### APPEARS IN

#### Related Questions VIEW ALL [5]

Solution for question: Prove that : ∫√(a2−x2)dx=x/2 √(a^2−x^2)=a^2/2 sin^−1(x/a)+c concept: Evaluation of Definite Integrals by Substitution. For the courses HSC Arts, HSC Science (Computer Science), HSC Science (Electronics), HSC Science (General)